Surgery for multiple endocrine neoplasia type 1-related insulinoma: long-term outcomes in a large international cohort. Issue 11 (30th April 2020) - Beek, D J; Nell, S; Verkooijen, H M; Borel Rinkes, I H M; Valk, G D; Vriens, M R; Goudet, P; Vella, A; Donegan, D; Bartsch, D K; Manoharan, J; Perrier, N D; et al.
Abstract: Background: Insulinomas are found in 10–15 per cent of patients with multiple endocrine neoplasia type 1 (MEN1) and lead to life-threatening hypoglycaemia. Surgical outcome and the optimal surgical strategy for MEN1-related insulinoma are unknown. Methods: Patients with MEN1-related insulinomas were identified in 46 centres in Europe and North America between 1990 and 2016. Insulinomas were considered localized if the lesion was in the pancreatic head or body/tail. Patients with pancreatic neuroendocrine tumours throughout the pancreas were suspected of having multifocal insulinoma. The primary outcome was postoperative hypoglycaemia, defined as persistent hypoglycaemia, or recurrent hypoglycaemia caused by a new insulinoma or insulin-producing liver metastases. Hypoglycaemia-free survival was estimated by the Kaplan–Meier method. Results: Ninety-six patients underwent resection for MEN1-related insulinoma. Sixty-three and 33 patients had localized and multifocal insulinomas respectively. After a median follow-up of 8 (range 1–22) years, one patient (1 per cent) had persistent disease and six (6 per cent) had developed recurrent disease, of whom four had a new insulinoma. The 10-year hypoglycaemia-free survival rate was 91 (95 per cent c.i. 80 to 96) per cent. Of those with localized disease, 46 patients underwent pancreatic resection and 17 enucleation. One of these patients had persistent disease and one developed recurrent insulinoma. Among patients with multifocal disease, three developed new insulinomas and two developed insulin-producing liver metastases. Conclusion: Surgery for MEN1-related insulinoma is more successful than previously thought. Graphical Abstract: In this cohort of 96 patients with resected multiple endocrine neoplasia 1 (MEN1)-related insulinomas, seven patients (7 per cent) developed postoperative persistent or recurrent hypoglycaemia after a median follow-up of 8 years. The 10-year hypoglycaemia-free survival rate was 91 (95 per cent c.i. 80 to 96) per cent. For patients with localized insulinoma, enucleation seems the preferred procedure. PPPD, pylorus-preserving pancreatoduodenectomy. Outcomes good